Perivascular mechanical environment: A narrative review of the role of externally applied mechanical force in the pathogenesis of atherosclerosis - Yamaguchi, Takashi; Morino, Katsutaro (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is promoted by systemic factors, such as dyslipidemia, hypertension, diabetes, and smoking, which cause atherosclerosis in blood vessels throughout the body. However, atherosclerotic lesions are characterized by their frequent occurrence in specific vessels and sites. Blood vessels are exposed to various mechanical forces related to blood pressure and flow. Although shear stress promotes the initiation and progression of atherosclerotic lesions, the pathogenesis of site specificity of atherosclerosis is not sufficiently explained by shear stress. We propose the concept of a perivascular mechanical environment (PVME). Compelling evidence suggests that site specificity in atherosclerotic lesions depends on a distinct local PVME. Atheroprone arteries, such as the coronary artery, are markedly affected by externally applied mechanical force (EMF), whereas atheroprotective arteries, such as the internal thoracic artery, are less affected. Recent studies have shown that the coronary artery is affected by cardiac muscle contraction, the carotid artery by the hyoid bone and the thyroid cartilage, and the abdominal aorta and lower extremity arteries by musculoskeletal motion. We speculate that the thoracic cage protects the internal thoracic artery from EMF owing to a favorable PVME. Furthermore, evidence suggests that plaque eccentricity is provided by EMF; plaques are frequently observed on an external force-applied side. In each vascular tree, site-specific characteristics of the PVME differ substantially, inducing individual atherogenicity. From the perspective of the mechanical environment, hemodynamic stress occurs in an inside-out manner, whereas EMF occurs in an outside-in manner. These inward and outward forces apply mechanical load individually, but interact synergistically. The concept of a PVME is a novel pathogenesis of atherosclerosis and also might be a pathogenesis of other arterial diseases.